Association of the geriatric nutritional risk index with poor outcomes in patients with coronary revascularization: a cohort study - Xie, Beili; Shi, Yue; Liu, Mingwang; Jin, Zhidie; Wen, Wei; Yan, Yuxin; Gao, Mengjie; Jiang, Lulian; Yang, Lin; Liu, Jiangang; Shi, Dazhuo; Zhao, Fuhai (Frontiers in Cardiovascular Medicine, 2024)
BackgroundPoor nutritional status may affect outcomes after coronary revascularization, but the association between nutritional status and outcomes in patients undergoing coronary revascularization has not been fully evaluated. This study was based on the MIMIC-IV database to analyze the impact of baseline nutritional status on poor outcomes in patients with coronary revascularization.MethodsPatients with coronary revascularization were screened from the MIMIC-IV database. A geriatric nutritional risk index (GNRI) was calculated and used to divide patients into 4 groups: no malnutrition (Q4: ≥96.79), mild malnutrition (Q3: 90.85–96.78), moderate malnutrition (Q2: 86.37–90.84), and severe malnutrition (Q1: 86.37). The primary outcome measure was 28-day mortality, and the secondary outcome measures were AKI and length of hospital stay. Cox proportional hazards model, Kaplan-Meier survival analysis, restricted cubic spline (RCS), and multiple linear regression model were used for statistical analysis, respectively, to ensure the robustness of study results.ResultsA total of 1,168 patients with coronary revascularization were included. The GNRI demonstrated a significant association with 28-day mortality in patients undergoing coronary revascularization. As a continuous variable, the GNRI exhibited a notable inverse correlation with mortality across unadjusted, partially adjusted, and fully adjusted Cox regression models [hazard ratios (HRs): 0.93, 0.94, 0.96, respectively; all P < 0.001]. When considered as a categorical variable, a low GNRI (first quartile, Q1) was significantly associated with elevated mortality risks (HRs: 2.64, 2.30, 1.82 in the unadjusted, partially adjusted, and fully adjusted models, respectively; all P < 0.05). Subgroup analysis revealed a more pronounced association in patients under 65 years of age (P for interaction = 0.014). Furthermore, reduced GNRI levels were also associated with an increased incidence of AKI and extended hospital lengths of stay.ConclusionGNRI is associated with prognosis in patients with coronary revascularization. Patients with lower GNRI had higher 28-day mortality, greater risk of AKI, and longer hospital stays.